2013
DOI: 10.4088/jcp.12m08328
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Diagnostic Change Among Patients Diagnosed With First-EpisodeDSM-IV-TRMajor Depressive Disorder With Psychotic Features

Abstract: Among patients who initially met DSM-IV-TR criteria for first-episode psychotic MDD, early indications of features typically associated with bipolar disorder or with nonaffective psychoses, respectively, strongly predicted later diagnostic change to bipolar disorder or schizoaffective disorders. The findings support the value of psychopathological details in improving diagnostic and prognostic criteria for complex illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 41 publications
1
35
1
Order By: Relevance
“…This finding is also consistent with findings reported by Salvatore et al (2013) in older adults and a study by Fiedorowicz et al (2011), documenting that subsyndromal symptoms of mania in patients with MDD of any age are predictive of manic switches. Likewise, Birmaher et al (2009) have documented that even minor manifestations of mania significantly increased the risk of development of fully syndromatic bipolar-I disorder over time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is also consistent with findings reported by Salvatore et al (2013) in older adults and a study by Fiedorowicz et al (2011), documenting that subsyndromal symptoms of mania in patients with MDD of any age are predictive of manic switches. Likewise, Birmaher et al (2009) have documented that even minor manifestations of mania significantly increased the risk of development of fully syndromatic bipolar-I disorder over time.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, Birmaher et al (2009) have documented that even minor manifestations of mania significantly increased the risk of development of fully syndromatic bipolar-I disorder over time. Whereas Strober et al (1982;1993) study is the only pediatric study that reported that the presence of psychotic symptoms in adolescents with MDD was a significant predictor of manic switching, there is a sizeable adult literature that documents that psychotic symptoms represent a strong predictor of manic switching (Akiskal et al, 1983;Coryell et al, 1995b;Fiedorowicz et al, 2011;Salvatore et al, 2013). It is noteworthy, however, that most of the reviewed studies excluded children with psychotic features during enrollment, limiting the scope of the available data for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The nonspecificity and variability of symptoms over time are frequent causes of misdiagnosis in patients with bipolar disorder (BD) [1, 2]. Although more frequent in BD, psychotic symptoms may be present in some patients with major depressive disorder (MDD) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to antecedent characteristics and affective presentations as risk factors for suicidal behavior, suicidal psychotic subjects were most likely to meet diagnostic criteria for bipolar mixed-states or psychotic major depression (Table 3). These mood-states, though separated by current nosological conventions, may be closely related in that manic-depressive mixed-states appear to have more in common with psychotic major depression than with mania [18,35,36,37]. This study is limited in the numbers of subjects and of suicide attempts in some psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…These assessments were made without preconceptions about the nature or timing of antecedent or presenting psychopathological phenomena in relation to type of presenting episode. The first author (PS) carried out comprehensive reviews of all available documents providing information about antecedent and first-episode clinical phenomena for all 516 first-episode psychotic subjects in random order over a three-year period, while held blind to initial and later diagnoses [17,18]. …”
Section: Methodsmentioning
confidence: 99%